Effect of relative humidity on the accuracy, scanning time, and number of photograms of dentate complete arch intraoral digital scans - Agustín Panadero, Rubén; Clemente Estada, María Isabel; Pérez Barquero, Jorge Alonso; Zubizarreta Macho, Álvaro; Revilla León, Marta; Gómez Polo, Miguel (My University, 2025)
Statement of problem Intraoral scanners (IOSs) have been used in dentistry for diagnostic and treatment purposes; however, the influence of environmental factors such as humidity or temperature on the accuracy of intraoral scanning is uncertain. Purpose The purpose of this in vitro study was to evaluate the influence of relative humidity and ambient temperature on the accuracy, scanning time, and number of photograms of dentate complete arch intraoral digital scans. Material and methods A completely dentate mandibular typodont was digitized by using a dental laboratory scanner. Four calibrated spheres were attached following the International Organization for Standardization (ISO) standard 20 896. A watertight box was designed to simulate 4 different relative humidity conditions (50%, 70%, 80%, and 90%) (n = 30). An IOS (TRIOS 3) was used to obtain a total of 120 complete arch digital scans (n = 120). Scanning time and number of photograms of each specimen were recorded. All the scans were exported and compared with the master cast by using a reverse engineering software program. The linear distances among the reference spheres were used to calculate trueness and precision. A unifactorial analysis of variance (ANOVA) and Levene tests followed by the post hoc Bonferroni test were used to analyze trueness and precision data, respectively. A unifactorial ANOVA followed by a post hoc Bonferroni test was also conducted to analyze scanning time and the number of photogram data. Results Statistically significant differences were found in trueness, precision, number of photograms, and scanning time (P<.05). Regarding trueness and precision, significant differences were found between the 50% and 70% relative humidity groups and the 80% and 90% relative humidity groups (P<.01). Regarding scanning time and number of photograms, significant differences were obtained among all groups, except between the 80% and 90% relative humidity groups (P<.01). Conclusions The relative humidity conditions tested influenced accuracy, scanning time, and number of photograms in complete arch intraoral digital scans. High relative humidity conditions resulted in the decreased scanning accuracy, longer scanning time, and greater number of photograms of complete arch intraoral digital scans.